Handbook of international electrical safety practices (Scrivener ; John Wiley & Sons, 2010)
A valuable and comprehensive safety reference for any organization working with or around electricity. This comprehensive guide informs working professionals in multiple industries, such as manufacturing, processing, or energy, about safety procedures that should be used on the job. It informs the reader about the hazards in the work place and what to do to make sure he/she is protected. The Handbook of International Electrical Safety Practices presents readers with the proper organizational skills needed to avoid hazardous injuries, details environmental monitoring technique.
Keywords: Electrical engineering -- Safety measures -- Handbooks, manuals, etc.; Electrical engineering -- Safety regulations -- Handbooks, manuals, etc.; Engineering.; Electricity.; Electric power.; elektronické knihy; electronic books